Operando X-ray photoelectron spectroscopy of solid electrolyte interphase formation and evolution in Li2S-P2S5 solid-state electrolytes - Kevin N. Wood (Nature Portfolio, 2018)
Solid-state electrolytes may improve the performance of batteries; however, many are unstable towards metallic lithium, and little is known about the chemical evolution of the interfaces that form during cycling. Here, the authors use an operando method to map the formation and evolution of a solid-electrolyte interphase during cycling.